2022
DOI: 10.3390/ijms23158140
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of Environmental, Individual and Genetic Factors in Rheumatoid Arthritis Provocation

Abstract: In this review, we explore systemization of knowledge about the triggering effects of non-genetic factors in pathogenic mechanisms that contribute to the development of rheumatoid arthritis (RA). Possible mechanisms involving environmental and individual factors in RA pathogenesis were analyzed, namely, infections, mental stress, sleep deprivation ecology, age, perinatal and gender factors, eating habits, obesity and smoking. The non-genetic factors modulate basic processes in the body with the impact of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 235 publications
0
8
0
Order By: Relevance
“…It is controversial whether the SARS-CoV-2 vaccine exacerbates autoimmune diseases including RA ( 4 , 18 ). While our study also cannot definitively establish whether the SARS-CoV-2 vaccine directly worsened RA, it is possible that mRNA vaccination could serve as an aggravating factor in RA as, for instance, smoking, obesity and environmental factors might ( 19 ). Recent study has shown the distinct different metabolic alterations of local lymph node stromal microenvironment in RA patients compared with healthy controls ( 20 ).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…It is controversial whether the SARS-CoV-2 vaccine exacerbates autoimmune diseases including RA ( 4 , 18 ). While our study also cannot definitively establish whether the SARS-CoV-2 vaccine directly worsened RA, it is possible that mRNA vaccination could serve as an aggravating factor in RA as, for instance, smoking, obesity and environmental factors might ( 19 ). Recent study has shown the distinct different metabolic alterations of local lymph node stromal microenvironment in RA patients compared with healthy controls ( 20 ).…”
Section: Discussionmentioning
confidence: 76%
“…Coronavirus Disease 2019 (COVID- 19) is an infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), a novel coronavirus discovered in Wuhan, China in December 2019 (1). COVID-19 causes flu-like symptoms such as fever and pharyngitis, but it can be severe, especially in the elderly or in those with underlying diseases such as diabetes, and can lead to acute respiratory distress syndrome, multiple organ failure and even death (2).…”
Section: Introductionmentioning
confidence: 99%
“…Our study further supports an interplay between HLA DRB1 * 07:01 and the immunomodulatory effect associated with alcohol consumption and childlessness in women. The paradoxical and beneficial effect of alcohol on RA was recently reviewed as well as its mechanism of action on the innate and adaptive immune systems that have predominant roles in RA ( 37 , 38 ). The relationship between childbirth and the risk of RA remains debated in the literature although it is well-established that RA often improves during pregnancy and flares can occur postpartum ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic as well as environmental factors play crucial roles in the onset of RA [12,[124][125][126][127][128][129][130][131]. Genetic factors, especially MHC II alleles carrying a "shared epitope" motif, were originally described to be associated with RA, although other genes such as peptidyl arginine deiminase (PAD) and protein tyrosine phosphatase non-receptor 22 (PTPN22) have been suggested to be associated with RA onset as well [12,128,130,[132][133][134].…”
Section: Rheumatoid Arthritismentioning
confidence: 99%